Tryptophan operon regulation in interspecific hybrids of enteric bacteria. - Manson, M D (1976)
We examined tryptophan regulation in merodiploid hybrids in which a plasmid carrying the trp operon of Escherichia was introduced into Trp mutants of other enteric genera, or in which a plasmid carrying the trpR+ (repressor) gene of E. coli was transfered into fully constitutive trpR mutants of other genera. In these hybrids the trp operon of one species is controlled by the repressor of a different species. Similar investigations were possible in transduction hybrids in which either the trp operon or the trpR+ locus of Shigella dysenteriae was introduced into E. coli. Our measurements of trp enzymes levels in repressed and nonrepressed cells indicate that Trp regulation is normal, with only minor quantitative variations, in hybrids between E coli and Shigella dysenteriae, Salmonella typhimurium, Klebsiella aerogenes, Serratia marcescens, and Proteus mirabilis. Our results support the idea that a repressor-operator mechanism for regulating trp messenger ribonucleic acid production evolved in a common ancestor of the enteric bacteria, and that this repressor-operator recognition has been conversed during the evolutionary divergence of the Enterobacteriaceae.